Concentration-Dependence of Vitamin C in Combinations with Vitamin E and Zeaxanthin on Light-Induced Toxicity to Retinal Pigment Epithelial Cells - Różanowska, Małgorzata (2012)
The purpose of this study was to determine the effects of increasing concentration of ascorbate alone and in combinations with α-tocopherol and zeaxanthin on phototoxicity to the retinal pigment epithelium. ARPE-19 cells were exposed to rose bengal and visible light in the presence and absence of antioxidants. Toxicity was quantified by an assay of cell reductive activity. 20 min exposure to visible light and photosensitizer decreased cell viability to ~42%. Lipophilic antioxidants increased viabilities to ~70%, ~61% and ~75% for α-tocopherol, zeaxanthin and their combination, respectively. Cell viabilities were ~70%, 56% and 5% after exposures in the presence of 0.35, 0.7 and 1.4 mM ascorbate, respectively. 45 min exposure increased cell death to ~74% and to >95% in the absence and presence of ascorbate, respectively. In the presence of ascorbate, zeaxanthin did not significantly affect phototoxicity. α-Tocopherol and its combination with zeaxanthin enhanced protective effects of ascorbate but did not prevent from ascorbate-mediated deleterious effects. In conclusion, there is a narrow range of concentrations and exposure times where ascorbate exerts photoprotective effects, exceeding which leads to ascorbate-mediated increase in photocytotoxicity. Vitamin E and its combination with zeaxanthin can enhance protective effects of ascorbate but do not ameliorate its deleterious effects.